Carburization induced extra-long rolling contact fatigue life of high carbon bearing steel. (February 2020) - Cao, Zhaoxi; Liu, Tianqi; Yu, Feng; Cao, Wenquan; Zhang, Xiaodan; Weng, Yuqing
Highlights: For the first time, carburization surface treatment is applied to high carbon bearing steel. Carburization introduces a gradient structure with plate/rod cementite in 100Cr6. RCF life of 100Cr6 is significantly enhanced by more than 10 times through carburization. Enhancement of RCF life is due to a combined effect of retained austenite and plate/rod cementite. Abstract: For the first time, vacuum carburization surface treatment was applied to high carbon bearing steel 100Cr6. The rolling contact fatigue (RCF) life and the wear behavior of 100Cr6 with and without carburization were compared and the microstructure was characterized. The carburization results in 30 vol% cementite and ~20 vol% retained austenite in the surface layer, significantly higher than those processed by the conventional heat treatment. RCF life ( L 10) is significantly enhanced by more than 10 times from 1 × 10 7 cycles to ≥1 × 10 8 cycles by carburization. This enhancement is attributed to plate/rod cementite and retained austenite.